The Effect Of Brand Image And Servicescape On Consumer Purchase Decisions In Indomaret Bengkulu Selatan - Fakhri Mustafa, Mufdhilul; Ayu Made Er Meytha Gayatri, Ida; Rahman Febliansa, Muhammad (Utami Publisher, 2024)
Marketing is a social and managerial process by which individuals and groups obtain what they need and want through creating, offering and exchanging products of value with others. The objectives to be achieved in this research are: a. To determine the effect of brand image on purchasing decisions at Indomaret Padang Damn Manna. b. This study aims to determine the effect of service speed on purchasing decisions at Indomaret Padang Sialang Manna. The sample in this study were 70 respondents. The method used in collecting data for this research is a questionnaire. The method of data analysis in this study is the Test of Multiple Linear Regression Research Instruments Hypothesis Determination Coefficient. Based on the results of this study, it was concluded that there was an effect of brand image (X1) on purchasing decisions (Y) because the tSig value for the variable (X1) was 0.012. So it can be concluded that tSig<Sig(0.002<0.050) and the value of tcount>ttable (3.963>1.6775) means that Ha is accepted and H0 is rejected, that the X1 variable has an effect on Y. Servicecape (X2) has an effect on purchasing decisions (Y) because the tSig value for the variable (X2) is 0.001. So it can be concluded that tSig<Sig (0.001<0.050) and the value of tcount>ttable (3.759>1.6775) means Ha is accepted and H0 is rejected. Brand image (X1), Servicescape (X2) has a positive and significant influence on purchasing decisions (Y ) Simultaneously because the calculated F is greater than the F table, namely 5.428 > 2.80 and Fsig < 0.05 (0.004 < 0.05)